PENGUATAN KARAKTER INTEGRITAS DAN GOTONG ROYONG BERBASIS SEKOLAH MELALUI KEGIATAN PRAMUKA - Septina Risa Yustina; Supriyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In this increasingly modern era, we are faced with a decline in noble national values such as honesty, mutual help, responsibility and so on. Several factors cause the decline in these values, namely people's mindset, the influence of foreign culture and rapid technological developments. An example of a decline in these grades is a lack of honesty among students, such as cheating on exams or copying other people's assignments. The decline in the value of helping each other can be seen in cases of rampant bullying and the lack of the value of responsibility which can be seen from students' lack of concern for their school assignments and obligations, such as being late in completing assignments and even not following school rules. These behaviors are not only detrimental to yourself, but if left unchecked they will become a habit and can harm other people. The aim of this research is to discuss strengthening the character of integrity and mutual cooperation through Scout activities carried out in elementary schools. This research uses descriptive qualitative methods using data triangulation techniques. From this research the results show that Scout extracurricular activities are activities that are suitable for strengthening students' character of integrity and mutual cooperation. The characters seen in this research include honesty, responsibility, justice, cooperation, solidarity, mutual help and respect